2016
DOI: 10.1108/sampj-12-2014-0092
|View full text |Cite
|
Sign up to set email alerts
|

Social impact measurement: why do stakeholders matter?

Abstract: Purpose – This paper aims to discuss the notion of social impact of social impact measurement in social enterprises by supporting the multiple-constituency theory as a contribution to this under-theorised issue. Moreover, the paper proposes the stakeholder-based approach as the most appropriate solution for selection among metrics related to the growing number of social impact measurements. Design/methodology/approach – The paper propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 49 publications
4
138
0
6
Order By: Relevance
“…Measurement standards should refer not only to attributes of measured objects, but also to guidelines concerning individual dispositions during the measurement process (i.e. Given the multifaceted nature of social value and the necessity to engage multiple stakeholders in the SVM process, authors have concluded that successful implementations require a host of approaches (Costa and Pesci 2016;Hall et al 2015;Polonsky and Grau 2011). Potential theoretical lens: institutional theory.…”
Section: Focus Of Svmi Research Svm Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement standards should refer not only to attributes of measured objects, but also to guidelines concerning individual dispositions during the measurement process (i.e. Given the multifaceted nature of social value and the necessity to engage multiple stakeholders in the SVM process, authors have concluded that successful implementations require a host of approaches (Costa and Pesci 2016;Hall et al 2015;Polonsky and Grau 2011). Potential theoretical lens: institutional theory.…”
Section: Focus Of Svmi Research Svm Toolsmentioning
confidence: 99%
“…Yet, while there are many approaches available to stakeholders interested in SVM (Maas and Liket 2011), few have been considered beneficial and appropriate for both internal and external stakeholders. This is despite consensus over the positive effects of internal stakeholder empowermentthrough SVM -on individual and organizational performance (Costa and Pesci 2016;Nguyen et al 2015;O'Dwyer 2005). This is despite consensus over the positive effects of internal stakeholder empowermentthrough SVM -on individual and organizational performance (Costa and Pesci 2016;Nguyen et al 2015;O'Dwyer 2005).…”
Section: Current Issues In Svm Researchmentioning
confidence: 99%
“…If managers decide to establish sustainability as an essential value of the organisation, their relationship with stakeholders should be established on that principle. If the stakeholder-firm relationship is grounded on trust, emotion, conscience and mutuality, complexity is reduced, making the relationship closer and stronger [39].…”
Section: Mutually Beneficial Relationships With Stakeholdersmentioning
confidence: 99%
“…Despite the growing importance of the nonprofit sector in providing public services in many developed countries, much remains to be understood in terms of its accounting and accountability mechanisms (Benjamin, ; Valentinov, ). What has to date been discussed is that nonprofit organizations (NPOs) have to respond to multiple stakeholders (Costa & Pesci, ) and therefore have to broaden their accountability mechanism in order to include mission achievement (Ryan, Mack, Tooley, & Irvine, ; Valentinov, ). In discussing broader accountability requirements for the nonprofit sector, many scholars have de‐emphasized the role of financial reporting information in favor of more nonfinancial information with a strong focus on mission and mission achievement (Ryan et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated social accountability in NPOs as a complex, multidirectional, and multistakeholder accountability process through which an organization measures and reports on its performance to multiple stakeholders (Brown & Moore, 2001;Costa & Pesci, 2016;Ebrahim, 2005;Knutsen & Brower, 2010;Najam, 1996). By investigating to whom NPOs should be/are accountable, many scholars have analyzed which stakeholders are affected by NPO activities-namely donors, funders, beneficiaries, workers, volunteers, and the members themselves (Ebrahim, 2003b;Najam, 1996;Ospina, Diaz, & O'Sullivan, 2002).…”
mentioning
confidence: 99%